(untitled) (Central Asian Journal of Medical Sciences, 2023)
Objectives: In the present study, we aimed to investigate the effect of Panzeria alaschanica Kupr. (P. alaschanica) on carrageenan-induced acute inflammation in rats. Method: Carrageenan-induced rat paw edema was used to evaluate the anti-inflammatory activity. P. alaschanica extract (32, 64, and 160 mg/kg/ BW) or vehicle was given orally 60 minutes before the subplantar injection of carrageenan. Ibuprofen (100 mg/kg) was used as a standard drug. The carrageenan-injected paw was measured 30, 60, 120, 180, and 240 minutes after the carrageenan injection. The levels of serum tumor necrosis factor (TNF)-α, interleukin (IL)-ELISA measured 1β, and IL-6. Results: The P. alaschanica at all given doses significantly (p˂0.01) inhibited carrageenan-induced rat paw edema. Moreover, it significantly reduced TNF-α, IL-1β, and IL-6 serum levels at different doses (p˂0.01). The anti-inflammatory effect of P. alaschanica was comparable to ibuprofen. Conclusion: P. alaschanica has an anti-inflammatory impact on carrageenan-induced paw edema in rats. The mechanism of action may partly be via reducing the levels of pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6.